Patient simulator to drive diagnostic thinking process and deep learning - P. L., Or, P.; C.F, So, H.; C.L.C, Leung; J.W.Y, Chung, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background The aim of this study was to evaluate clinical reasoning of the diagnostic thinking process among student nurses in pre-enrollment nursing programs in two different educational institutions using a patient simulator. Method This study adopted a quasi-experimental design. Problem behavior graphs (PBGs) were drawn to reflect the participants’ clinical reasoning processes. Biggs’ Study Process Questionnaire (SPQ) was used to evaluate their study approaches into six sub-scales. Results Forty-two subjects were randomly drawn from students of two pre-enrollment nursing programs: 21 from a college and 21 from a hospital-based nursing school. Subjects from the college had more data driven strategy (53%) in the problem behavior graphs (PBGs). They used more surface strategy than subjects from the nursing school (47%). Conclusions Results pinpoint data-driven strategy in nursing education helps to improve the current nursing education in Hong Kong. Only if the ability to master diagnostic thinking process from student nurses ensures patient safety in clinical environments.